Hydrogen Sulfide Prevents Mesenteric Adipose Tissue Damage, Endothelial Dysfunction, and Redox Imbalance From High Fructose Diet-Induced Injury in Aged Rats - Revenko, Oleh; Pavlovskiy, Yaroslav; Savytska, Maryana; Yashchenko, Antonina; Kovalyshyn, Vasyl; Chelpanova, Ilona; Varyvoda, Olena; Zayachkivska, Oksana (Frontiers in Pharmacology, 2021)
A high fructose diet (HFD) and advanced age are key factors for the gradual loss of physiological integrity of adipose tissue. Endogenous hydrogen sulfide (H2S) has beneficial effects on cytoprotection and redox balance. But its interactive effects on age-related damage of mesenteric vessels and connective and adipose tissues (MA) during HFD which could be the base of the development of effective physiological-based therapeutic strategy are unknown. The aim of study was to investigate age- and HFD-induced mesenteric cellular changes and activities of enzymes in H2S synthesis and to test the effects of sodium hydrosulfide (NaHS) which is considered an H2S donor on them. Adult and aged male rats on a standard diet (SD) or 4-week HFD were exposed to acute water-immersion restraint stress (WIRS) for evaluation of mesenteric subcellular and cellular adaptive responses by electron microscopy. The effects of exogenous NaHS (5.6 mg/kg/day for 9 days) versus vehicle on mesentery changes were investigated. Serum glucose level, thiobarbituric acid reactive substances (TBARS), and activities of cystathionine γ-lyase (CSE) and cystathionine β-synthase (CBS), thiosulfate-dithiol sulfurtransferase (TST), and sulfite oxidase (SO) were examined by spectrophotometry. In both adult and aged SD groups, treatment with NaHS protected mesenteric cells after WIRS. In both groups, the treatment with NaHS also protected MA mitochondria, microvascular endothelial and sub-endothelial structures, and fibroblasts versus the vehicle-treated group that had signs of damage. HFD increased MA injury and mitochondrial changes in both aged and adult rats. HFD-associated malfunction is characterized by low activities of CSE, CBS, TST, SO, and increased TBARS. Finally, we demonstrated that pretreatment with NaHS inhibited MA and mitochondria alterations in aged rats exposed to HFD and WIRS, lowered TBARS, and enhanced H2S enzyme activities in contrast to the vehicle-treated group. Mitochondrial integrity alterations, endothelial damage, and redox imbalance are key factors for rat mesenteric adipose tissue damage during advanced age. These alterations and MA hypertrophic changes retain the central for HFD-induced damage. Moreover, H2S signaling contributes to MA and mitochondria redox balance that is crucial for advanced age and HFD injury. The future study of H2S donors’ effects on mesenteric cells is fundamental to define novel therapeutic strategies against metabolic changes.